Patterns of Care and Outcome of Clear Cell Carcinoma of the Head and Neck. (12th March 2019) - Oliver, Jamie; Wu, Peter; Chang, Clifford; Roden, Dylan; Wang, Binhuan; Liu, Cheng; Hu, Kenneth; Schreiber, David; Givi, Babak
Abstract : Objective: Clear cell carcinoma (CCC) is a rare salivary gland malignancy, believed to be generally low grade. We investigated CCC epidemiology and clinical behavior, using the National Cancer Database (NCDB). Study Design: Retrospective cohort study. Setting: NCDB. Subjects and Methods: All CCCs of the salivary glands were selected between 2004 and 2015. Patient demographics, tumor characteristics, treatments, and survival were analyzed. Cox regression analyses were performed in treated patients. Results: We identified 268 patients with CCC. Median age was 61 (21‐90) years. Most were female (145, 54%). The most common site was oral cavity (119, 44%), followed by major salivary glands (68, 25%) and oropharynx (41, 15%). Most tumors were low grade (81, 68%) and stages I to II (117, 60.6%). Nodal (36, 17.5%) and distant metastases (6, 2.4%) were rare. Most were treated by surgery alone (134, 50.0%), followed by surgery and radiotherapy (69, 25.7%). Five‐year overall survival (OS) was 77.6% (95% CI, 71.4%‐84.2%). In univariate analysis, older age, major salivary gland and sinonasal site, stages III to IV, high grade, and positive margins were associated with worse OS. In multivariate analysis, only high tumor grade (hazard ratio [HR], 5.76; 95% CI, 1.39‐23.85; P =. 02), positive margins (HR, 4.01; 95% CI, 1.20‐13.43; P =. 02), and age ≥60 years (HR, 3.45; 95% CI, 1.39‐8.55; P =. 01) were significantly associated with OS. Conclusion: We report the largest series of clear cell carcinomas of the head and neck. Outcomes are generally favorable following surgical‐based treatments. In this series, pathologic tumor grade is associated with worse survival. Routine evaluation and reporting of tumor grade might better guide physicians in recommending appropriate treatments in this rare malignancy.